HUKUM DAN PERTUMBUHAN EKONOMI: KASUS INDONESIA DALAM PERSPEKTIF EKONOMI ISLAM - Wahyu, Bambang (Al-Infaq: Jurnal Ekonomi Islam, 2011)
This paper is aimed to provide the important way to relate economics growth under the law. The problem of economics growth which has no significant result to many countries economics development is lied on decoupling between macroeconomics and microeconomics. Government took widely way to market to decide economic growth roll so created a negative effect to gross domestic product, unemployment and poverty numbers. In Islam, government has a function as regulatory law in order to enforce and control market mechanism to attain effectively economic growth.